Developing corporate entrepreneurship in the National Health Service: a study of a large East Midlands trust - Johnson, Dyneshia A. (2016)
The goal of this dissertation is to motivate a cognitive based view of corporate entrepreneurship (CE) propagation. In doing so, it advocates that the literature requires a more in-depth view of how organisational members choose to instigate or participate in entrepreneurial behaviour within the organisation confines. In addition to what organisational contextual factors bear on this decision making process. As such I move away from the top-down organisational level of analysis perspective that dominates the field and re-focus on the ‘individual in CE.’ To achieve this, I draw on socio-cognitive perspectives and the growing body of work on cognitive mechanisms in entrepreneurship research (Baron, 1998). Specifically, I utilise the entrepreneurial cognition entrepreneurial intentions (EI) as the best predictor of entrepreneurial behaviour and the EI formation model Shapero’s Entrepreneurial Event (SEE), (Krueger, 1993; Shapero, 1982) to understand how organisational members choose to act entrepreneurially.